Deep and partial immunoparesis is a poor prognostic factor for newly diagnosed multiple myeloma patients. Issue 4 (21st March 2021) - Geng, Chuanying; Yang, Guangzhong; Wang, Huijuan; Wu, Yin; Leng, Yun; Zhou, Huixing; Zhang, Zhiyao; Jian, Yuan; Chen, Wenming
Abstract: We retrospectively analyzed immunosuppression status in 287 newly diagnosed multiple myeloma (MM) patients and assessed the prognostic value of immunoparesis on survival. Deep immunoparesis was defined that one of uninvolved immunoglobulins was below 50% the lower limit of normal ranges, partial immunoparesis was defined at least two suppressed uninvolved immunoglobulins. We found that patients with deep and partial immunoparesis had a significantly shorter median overall survival (OS) and progression-free survival (PFS). Moreover, deep and partial immunoparesis was a poor prognostic factor for OS and PFS in univariate and multivariable analyses. To reduce the bias between the groups, we performed a 1:1 propensity score matching technique for analysis and found that patients with deep and partial immunoparesis also had shorter OS and PFS. Our study showed that deep and partial immunoparesis can be defined an independent poor prognostic factor for patients with newly diagnosed MM.